SOME TYPOLOGIES OF EDUCATIONAL INSTITUTIONS OF PAK. REGARDING DIFFERENCES IN EDUCATIONAL STANDARD (ANALYTICAL STUDY OF PRINTED MEDIA) - Ali, Dr. Hafiz Nasir; Ashraf, Dr.Muhammad; Mahmood, Dr. Tariq; Amin, Dr. Muhammad (The journal of contemporary issues in business and government, 2021)
In this paper, some typologies of educational system of Pakistan are discussed which are elaborated which are elaborated by column writers and editors of printed media of Pakistan in different newspapers from the year 2010 to 2014. The purpose of this paper is to point out weak aspects of our educational system so that improvement for these weak aspects might be dome. In this way the fruit full results in education sector may be gained. In this paper, status of teacher for improving our educational atmosphere is also discussed for societal and economic changes in curriculum for gaining real development. In short, this paper presents some differences in educational sector and the facilities and standard of education because of teachers’ ability and capability also.